(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Undergraduate medical education aims at sculpting the future physicians. Knowledge gained from here will help them to act effectively when they will face different medical problem in future. It is necessary to ensure that students learn what is important and thus it is very important to assess them with right question in the examination. Methods: This is a retrospective analytical study involving evaluation of 2nd professional MBBS pharmacology written (SAQ) questions held in four universities (Dhaka, Chittagong, Sylhet shahjalal and Rajshahi) of Bangladesh. Written (SAQ) question from July 2008 to July 2016 were analyzed for content coverage, type of question, educational objectives as per 2002 curriculum. Results: Total 56 written questions were analyzed. Each question contains 24 items SAQ arranged in four groups. On the basis of content coverage chemotherapeutic (19%), CNS (16%), GP (15%) and ANS(10%) are the maximum weightage of content area. Some aspect which are clinically important but less practiced in written examination are GIT, respiratory, renal, hemopoietics, lipid lowering agents and miscellaneous. Though the entire question should be SAQ type but some (4%) portion of question became essay type and short notes (5-10%) also common. Most of the questions were recall (90%) type, problem solving questions only 2%. Conclusion: It can be concluded that assessment instrument should be based on structured guidelines to improve the quality of question. To maintain consistency among different university periodic analysis of written questions, test blue printing and table of specification may be used. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 13-17